(untitled) (KYAMC Journal, 2017)
Type 2 diabetes is a common, chronic disease with a prevalence that is increasing at epidemic proportions. Management involves advice on lifestyle changes, oral anti-hyperglycaemic agents and/or insulin. The kidney plays an important role in glucose homeostasis via its production, utilization, and, most importantly, reabsorption of glucose from glomerular filtrate which is largely mediated via the sodium glucose cotransporter 2 (SGLT2). Competitive inhibition of SGLT2 induces glucosuria in a dose dependent manner and appears to have beneficial effects on glucose regulation in individuals with type 2 diabetes. Agents that inhibit SGLT2 represent a novel class of drugs, which has recently become available for treatment of type 2 diabetes. This article summarizes the rationale for use of these agents and reviews available clinical data on their efficacy, safety, and risks/benefits. KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 592-597